An Analysis of Students’ Ability of Degree of Comparison in Writing Simple Sentences at Eighth Grade - Oktapiani, Sri; Putri, Dwi Megista (SAFE-Network, 2024)
This study uses a descriptive design in describing the abilities of students in grade VIII of Junior High School. The ability studied is the ability of students' comparative level in writing simple sentences using English. The ability tested is the degree of comparison of adjectives by giving students a writing test. The data was processed from taking convenience sampling of 20 students who were active in class. The test site was grade VIII students at the State Islamic Junior High School (MTsN) 5 Tebo. The researcher classified students' abilities based on the Madrasah Working Group (KKM) with a standard value of 75 (seventy-five). Students who have a score below 75 (seventy-five), are declared to have low abilities and those who have higher scores are declared to have high abilities. The test results are students with high abilities amounting to 15% who can write simple sentences using degrees of comparison in adjectives. Students with low abilities are 85% who cannot write simple sentences using degrees of comparison in adjectives. So, this study can be a reference in providing lessons on the ability to write simple sentences using adjectives to students in grade VIII of Junior High School.